PENGARUH FINANCIAL DISTRESS, INTENSITAS MODAL, LEVERAGE, DAN PROFITABILITAS TERHADAP KONSERVATISME AKUNTANSI - Welni Rafida; Yolanda Pratami (Journal Of Islamic Finance And Accounting Research, 2023)
This study is entitled The Effect of Financial Distress, Capital Intensity. Leverage, and Profitability On The Accounting Conservatism (Empirical Study of Property and Real Estate Companies Listed on The Indonesian Stock Exchange For The 2019-2021 Period). This study aims to determine the effect of financial distress, capital intensity, leverage, and profitability on the accounting conservatism. This research is quantitative research with a descriptive approach. The population in this study amounted to 20 property and real estate companies listed on The Indonesian Stock Exchange for the 2019-2021 period. The research sample was selected using a purposive sampling technique in order to obtain 20 companies that met the criteria during the 2019-2021 time span. Data analysis using multiple linear regression analysis technique. Based on the results of the data analysis carried out, it show that the financial distress, capital intensity, and leverage significantly effect on accounting conservatism. The variable profitability has no significant effect on accounting conservatism. Simultaneously, the variable of financial distress, capital intensity, leverage, and profitability significantly effect on accounting conservatism.